INTERNET DAN PERANNYA PADA KEMAMPUAN MAHASISWA DALAM MENERJEMAHKAN - Ayu Rizki Septiana; Moh Hanafi (Jurnal Akrab Juara, 2018)
This research was aimed to find out the role of internet in translating. The subject of this research was the students who took Translation course. The data in this research were taken in three methods that is observation, interview and questionnaire. Based on the result of data analysis, it was found that in the Translation course, the students had freedom on using internet to translate. Internet was believed by the students to be helpful on their ability to translate, especially in translating in more natural way. Moreover, the students used search engines such as google and yahoo, read articles in English, and used online dictionary. However, they tend to be not satisfy with the translation result of the google translate. Therefore, the first conclusion that can be taken is that the ability of the students to translate is good enough. It was proven by the mean score of the class which reached 78.67. The second conclusion is that the internet is quite helpful for the students to help them translating the material. Keywords: internet, translation ability, qualitative research.